Pengaruh Pengendalian Kredit Terhadap Kesehatan Bank pada PT. Bank Bukopin Tbk Cabang Cendrawasih Kota Makassar - Maryadi, Maryadi (Jurnal Ilmiah Ilmu Administrasi Publik, 2017)
The aim of this research was to analyze the effect of Influence of Preventive Control of Credit and Repressive Control of Credit to the health of PT. Bukopin Bank Tbk, sub branch office of Cendrawasih, Makassar City. The researcher used questionnare as a technique of data collection and used technique of data analysis of multiple linear regression. The population of this research was 50 participants and the number of samples were all the populations 50 people. The result of this research showed that Preventive Control of Credit and Repressive Control of Credit influenced to the health of bank simultaneously, where the testing result was got F 8,144 > F table 3,20. The result had been got partially showed Preventive Control of Credit was significant to the health of bank by looking at t 3,987 > t table 1,677 and sig 0,000 < 0,05 while Repressive Control of Credit was not significant to the health of bank by looking at t 0,067 < t table 1,677 and sig 0,947 > 0,05, and coefficient of determination (adjust R2) showed independent variable of percentage can influence independent variable was 25,7%, so the balance was 74,3% affected by the other variable that not researched in this research.